A Panoramic Potential Applications of an Alternative Cooling Opportunities for Automobiles - Sandeep Shalgar*, Rupa Bindu (International Journal of Advanced Science and Technology, 2020)
With the rapid changing environment and atmospheric effect, the air conditioning of the movingvehicle has become a necessity. Cooling demand is rapidly increasing across the world and thusincreases the power consumption. Such increase in cooling demands threatens the internationalagreements on CO2 emission, since consumption of fossil fuel has increased to meet the demand. Alsoregulations to restrict use of harmful CFCs and HFCs for reducing greenhouse gases and ozonedepletion need to be followed strictly. In view of this one should restrict usage of refrigerant tominimum and increase the use of natural resources. The challenges of effective optimization ofalternative cooling technique to current vapor compression cycle is still global raising bar, thoughresearcher practices many years. The system COP enhancement, heat transfer effectiveness,component sizing, material selection and design considerations are key take away for new researchers.This paper focuses panorama on a potential applications of alternative cooling techniques toautomobiles for implementation. As a result of review the main knowledge gaps for automobileapplication, integration and strategies are mentioned. The potential future opportunities ofimplementation of evaporative cooling system are explained in prolong depth with the designconsiderations and layout